Internationalization in the information age: A new era for places, firms, and international business networks? - Alcácer, Juan; Cantwell, John; Piscitello, Lucia (Journal of International Business Studies, 2016)
The new techno-economic paradigm of the information age has brought about new structures and processes in international business (IB). In this article, we examine the changing nature of the competitive advantages of places, the competitive advantages and strategies of firms, and the governance structure of IB networks in what has also been called the third industrial revolution. These three areas of change in IB activities can be mapped respectively to the location (L), ownership (O) and internalization (I) advantages of the eclectic paradigm. We interpret these OLI factors as dynamic constructs in order to depict analytically the shifts in the IB environment and their implications for IB.